Toward a pedagogy of connection: A critical view of being relational in listening. Issue 1 (February 2022) - Hinz, Jessi; Stephens, John Paul; Van Oosten, Ellen B
Positive Organizational Scholarship (POS) perspectives define interpersonal work experiences such as positive work relationships and high-quality connections by the mutual growth and empowerment experienced by relationship or connection partners. Listening has been implicated as a key mechanism for building such positive interpersonal work experiences, but it is unclear how listening spurs on mutual, rather than one-sided growth, in relationship and connection partners. In this paper, we argue that management education currently focuses on the intrapersonal capability of listeners to execute key verbal and non-verbal behaviors. Less emphasis is placed on the mutual experience co-created between speaker and listener and, thus, on the potential for mutual growth and empowerment. We articulate what "being relational" in the listening experience means, and use experiential learning theory to articulate how educators might create learning spaces for "being relational" through conversations between listener and speaker. Throughout the paper we contend with issues of individual and structural power asymmetries inherent in understanding listening as a relational process.